MENGENAL CYBERBULLYING MEDIA SOSIAL : PENYEBAB, DAMPAK DAN SOLUSINYA - Farizy , Salman; suharto, Agus; Fahrudin , Endin (PT Triputra Sejahtera Prima, 2025)
Cyberbullying on social media is a serious problem that can have a negative impact on victims. The main causes of cyberbullying include anonymity in cyberspace, lack of empathy, and abuse of freedom of speech. This phenomenon has a serious impact on the mental and social health of victims, such as decreased self-confidence, anxiety disorders, depression, and in some extreme cases can even encourage victims to withdraw from social circles or commit self-harm. To overcome this, digital education is needed, which we conducted through Community Service activities at the Kedaung youth organization, Sawangan District, Depok City, West Java, at the Parigi Reading Park. The objectives of the Community Service Program (PKM) were to introduce cyberbullying, identify the causes of cyberbullying on social media, analyze the impact of cyberbullying on victims, and find solutions to overcome cyberbullying on social media. The results of the PKM activity fostered empathy and moral awareness among participants to be wiser and more responsible in communicating in the digital space. The participants' active involvement in discussions, simulation exercises, and digital campaigns demonstrated that this activity was not only informative but also transformational in changing participants' perspectives and behaviors regarding the issue of online bullying. The target outputs were activity videos, articles in print or online media, and scientific journal articles on community service. Keywords: Socialization, Solutions, Cyberbullying; Social Media